Utilization of modern contraceptive methods among women of reproductive age in Senegal: A multilevel mixed-effects analysis - Hiwot Tezera Endale; Habtu Kifle Negash; Winta Tesfaye; Fethiya Seid Hasen; Tseganesh Asefa; Destaye Tirite Gelaw; Yihun Tefera Ayenew; Nebebe Demis Baykemagn; Tirualem Zeleke Yehuala; Mihret Getnet (PLoS ONE, 2025)
Background Despite high fertility rates in low- and middle-income countries, modern contraceptive use remains low. In Senegal, there is limited use of modern contraceptives, and few studies have explored the factors influencing their adoption. This study aims to identify the determinants of modern contraceptive use among women of reproductive age in Senegal. Method Data from the 2023 Senegal Demographic and Health Survey, covering 8,833 women, were analyzed using a multilevel logistic regression model to identify factors associated with modern contraceptive use. Adjusted odds ratios (AORs) with 95% confidence intervals (CIs) were used, and statistical significance was set at p < 0.05. Analysis was conducted using STATA version 17. Results The utilization of modern contraceptives among reproductive-aged women in Senegal was 32.16% (95% CI: 31.19, 33.15). Significant factors associated with its use included age (25–34: AOR = 1.46, 35–44: AOR = 1.59, > 44: AOR = 1.72), secondary education (AOR = 1.19), employment (AOR = 1.38), being undecided about having more children (AOR = 1.39), not wanting more children (AOR = 2.42), age at first sex (≥18: AOR = 1.16), and first birth (≥19: AOR = 0.65). Other factors include being visited by a field worker (AOR = 1.32), visiting a health facility (AOR = 2.04), media exposure (AOR = 1.42), higher household income (middle: AOR = 1.23, rich: AOR = 1.38), and having one or more births (one: AOR = 2.06, two or more: AOR = 1.72). Women living in rural areas (AOR = 0.75) or in regions such as Ziguinchor (AOR = 0.60), Diourbel (AOR = 0.50), Tambacounda (AOR = 0.27), Louga (AOR = 0.61), Matam (AOR = 0.37), Kédougou (AOR = 0.64), and Sédhiou (AOR = 0.67) were less likely to use contraceptives. Conclusion Factors such as age, education, employment, media exposure, and healthcare access are critical determinants of modern contraceptive use in Senegal. Women in rural areas and specific regions face barriers to contraceptive use. Targeted interventions in these areas could enhance family planning and reproductive health outcomes in Senegal.